Federalismo sem pactuaç\~ao: Governos estaduais na antessala da federaç\~ao - Aristides Monteiro Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This article aims to investigate the origin of unbalances and tensions between central and subnational governments concerned to the allocation of resources and decentralization of public policies. One argue that Brazilian federalism in recent years (2000-2012) has establishing a high level of centralization in two essential dimensions of intergovernmental relations - contributing to tensions and negative reactions in subnational governments, particularly on the state or provincial governments. Firstly, the high degree of centralization of fiscal resources by central government. Secondly, the increasing control, at central level, of capabilities and initiatives for designing and implementing public policies. These two characteristics of centralization degree mean that subnational levels of government are prone to have a reduced and limited role in our federalism in contrast to constitutional prescriptions.
Keywords: H77; H11; R11; 330; intergovernmental relations; federalism; governance capabilities; state/provincial levels of government; regional and local development